Investigation of Chronic Obstructive Pulmonary Disease (COPD) Development in Terms of Urea, Creatinine and Some Blood Parameters in Patients with Allergic Rhinitis - Akduman, Seha (International Journal of Innovative Research in Medical Science, 2019)
Aim: In this retrospective crossectional study, it was aimed to evaluate the development of COPD in terms of urea, creatinine and some blood parameters in patients with allergic rhinitis. Method: Patients who were admitted to Kadıköy Medicana Hospital between 12.10.2017 and 12.10.2018 with respiratory complaints and has COPD diagnosis for the first time were evaluated retrospectively. Among the 845 patients admitted to the clinic for a one-year period, 160 patients with the diagnosis of COPD for the first time and 42 patients with a history of allergic rhinitis were subjected. The study group consisted of 63 patients with COPD who were diagnosed as COPD for the first time but without allergic rhinitis and 57 allergic rhinitis patients with no diagnosis of COPD. Findings: CRP, urea, WBC and neutrophil levels were higher in COPD group; creatinine and eisonofil levels were higher in COPD-Allergic rhinitis group and HGB was higher in the allergic rhinitis group. The differences between CRP and urea levels of COPD and allergic rhinitis group were statistically significant (p <0.05). The urea values were significantly different between COPD + allergic rhinitis and COPD groups (p <0.05). According to the results of ROC analysis, the value of urea for the COPD + allergic rhinitis group was statistically insignificant (p> 0.05), whereas it was statistically significant for the allergic rhinitis group (p <0.05). Conclusion: In detecting the difference between allergic rhinitis and COPD associated allergic rhinitis, urea levels may have a diagnostic value. An increase in urea in patients with allergic rhinitis may indicate comorbid COPD.